Diagnosis and Management of Osteoporosis in Children and Adolescents - Hye Young Jin; Eu Seon Noh; Il Tae Hwang (The Ewha Medical Journal)
Recent advances in medicine have led to an increase in the number of children and adolescents treated for various chronic diseases and cancer. Increasingly sophisticated genetic analysis techniques have also clarified some genetic factors that contribute to bone fragility. Osteoporosis, characterized by reduced bone mass and skeletal fragility, can result from primary or secondary causes that originate in childhood and adolescence, which are critical periods for bone mineral acquisition. It is essential to identify children and adolescents at risk of fractures due to osteoporosis, and early intervention is crucial. Conservative management strategies, such as treating underlying diseases, replacing deficient hormones, providing nutritional support to meet calcium and vitamin D requirements, and encouraging regular physical activity, should be prioritized. Pharmacological treatment should be initiated in a timely manner following a comprehensive bone health examination. Intravenous pamidronate therapy has been safely and effectively administered to children and adolescents, although long-term follow-up is necessary. Further investigation is needed regarding bone fragility fractures of unknown etiology and the application of new medications for pediatric use.